Newborn bloodspot screening policy framework for Australia - O'Leary, P.; Maxwell, Susannah (2015)
Background: The aim of newborn bloodspot screening (NBS) is to identify rare genetic and non - genetic conditions in children soon after birth in order to commence therapies that prevent the development of progressive, serious, and irreversible disabilities. Universal NBS program me s have been implemented in most countries, with minor adaptations to target conditions most relevant to the local healthcare environment. Aims: In this article, we describe the initiative s of international and Australian governments to develop policies to address the expansion of NBS in their healthcare systems. Methods: We have reviewed published public policies and literature to formulate recommendations based on clinical, social, legal, and ethical principles to inform a national governance and policy framework for Australia. Results: Australia n policy makers have been slow to develop a coordinated plan. While the experience from other governments can guide our national policy, there are specific areas that require further consideration by Australian health experts. Key reforms involve the separation of policy and operational activities, multidisciplinary decision - making and oversight by the Australian Health Ministers’ Advisory Council for policy direction. Conclusion: A formal national policy framework will guide the coordination of NBS service s that can adapt to the needs of Australian children and families.